2004
DOI: 10.1590/s0100-29452004000300038
|View full text |Cite
|
Sign up to set email alerts
|

Característica da germinação e morfologia do endocarpo e plântula de taperebá (Spondias mombin L.) - Anacardiaceae

Abstract: RESUMO -O taperebá (Spondias mombin L.) é uma espécie frutífera bastante apreciada no Norte e Nordeste do País. Porém, alguns problemas fitotécnicos ainda persistem, dentre os quais a germinação irregular e distribuída ao longo do tempo. O objetivo deste trabalho foi estudar as características de germinação das sementes, indicando algumas causas que contribuem para a baixa germinação das sementes, além de contribuir com a produção de mudas de boa qualidade. O trabalho foi desenvolvido sob condições ambientais … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 2 publications
0
9
0
9
Order By: Relevance
“…Therefore, the increased demand for yellow mombin fruits has attracted interest to the cultivation of this species, which is still considered in the process of domestication with little information about the establishment of commercial orchards (SOUZA et al, 2006). Its inclusion as a fruit species in the modern agronomic models requires, however, the identification of propagated materials whose genotypes that in addition to having high productive capacity (AZEVEDO; MENDES; FIGUEIREDO, 2004;CASSIMIRO;MACÊDO;MENINO, 2009;SOUZA et al, 2010) can produce fruits with superior functional quality (SOARES et al, 2006;DANTAS JÚNIOR, 2008).…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…Therefore, the increased demand for yellow mombin fruits has attracted interest to the cultivation of this species, which is still considered in the process of domestication with little information about the establishment of commercial orchards (SOUZA et al, 2006). Its inclusion as a fruit species in the modern agronomic models requires, however, the identification of propagated materials whose genotypes that in addition to having high productive capacity (AZEVEDO; MENDES; FIGUEIREDO, 2004;CASSIMIRO;MACÊDO;MENINO, 2009;SOUZA et al, 2010) can produce fruits with superior functional quality (SOARES et al, 2006;DANTAS JÚNIOR, 2008).…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…Os frutos são comercializados e podem ser consumidos "in natura" ou na forma de sucos, sorvetes, picolés e cremes (QUEIROZ, 2000;AZEVEDO et al, 2004).…”
Section: Tratamento Térmico De Frutos Da Cajazeira Utilizando Vapor Dunclassified
“…Depending on its precedence, the nuculanium may be of different sizes with a length from 25.2 to 34.8 mm and a diameter between 13.2 and 21.2 mm (SOUZA et al, 2000;MENDES;FIGUEIREDO, 2004). Nuculanium size may be related to the speed of germination; Azevedo, Mendes and Figueiredo (2004) reported that the largest diaspores bear seeds which primary roots are emitted more promptly than those of the smaller diaspores. It is supposed that the larger nuculania were, during their formation, more well-nourished and thus have more vigorous seeds.…”
Section: Introductionmentioning
confidence: 99%